Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the ease of finding reliable answers to your questions from a vast community of knowledgeable experts. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
[tex]f(x)=3x+2 \\
g(x)=2x-2 \\ \\
(f-g)(x)=f(x)-g(x)=3x+2-(2x-2)=3x+2-2x+2=\\
=x+4 \\ \\
\boxed{(f-g)(x)=x+4}[/tex]
I would assume that you subsitute as usual, but g is negative
(f-g)(x)=(3x+2)-(2x-2)
(f-g)(x)=3x+2-2x+2
(f-g)(x)=x+4
(f-g)(x)=(3x+2)-(2x-2)
(f-g)(x)=3x+2-2x+2
(f-g)(x)=x+4
We appreciate your time. Please revisit us for more reliable answers to any questions you may have. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.